Factors Affecting Students’ Use of Mobile Banking: An Extension of Technology Acceptance Model - Susilowati, Endah; Auliah, Alfiah Nur (JASF: Journal of Accounting and Strategic Finance, 2023)
Current developments in technology and communications have created various types and new business opportunities, so it is very important for companies to carefully understand customer needs, discover people's desires, and be able to provide products or services to customers that meet people's demands or exceed people's expectations. This study aims to test and prove the factors that influence the use of mobile banking, which consists of the quality of information systems, trust, capability of individual operations, user attitudes, and intention to use. This study assesses the technology acceptance model (TAM) theory to develop variable relationships. The study population was active students of a university in East Java, and the sample was taken by purposive sampling with a total sample of 91 students. This research uses a quantitative approach and questionnaire data collection methods. Data analysis techniques using multiple linear analysis with SPSS 23 software. The results of this study indicate that trust, individual capability to operate, and intention to use affect mobile banking use. In contrast, the quality of information systems and user attitudes do not affect the use of mobile banking. This study suggests that mobile banking providers must maintain consumers’ trust, capability to operate, and attitude so that the use of mobile banking is increased.